2021
DOI: 10.1002/eng2.12404
|View full text |Cite
|
Sign up to set email alerts
|

Energy, exergy, and economic analysis of an integrated solar combined cycle power plant

Abstract: Integrated Solar Combined Cycle (ISCC) power plants based on Parabolic Trough Concentrators (PTCs) are the most efficient way for solar into electrical energy conversion. However, due to operation in several climate conditions, they need more efforts in their adaptation. This paper presents a techno‐economic assessment of an ISCC ‐ PTC system operating at Hassi R'mel site (Algerian Sahara) for which a new thermal storage system is incorporated. The obtained results reveal noticeable enhancements in the solar e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The model was able to reproduce most of the operating parameters, such as pressure, temperature, mass flow rates and output power. An economic and performance assessment of the ISCC-PTC system in Hassi R'mel (Algeria), coupled with a new thermal storage system was performed [20]. Results revealed that a better grid stability was reached, increasing solar energy conversion and overall performance.…”
Section: Solar Integration In Combined Power Plants and Research Ques...mentioning
confidence: 99%
“…The model was able to reproduce most of the operating parameters, such as pressure, temperature, mass flow rates and output power. An economic and performance assessment of the ISCC-PTC system in Hassi R'mel (Algeria), coupled with a new thermal storage system was performed [20]. Results revealed that a better grid stability was reached, increasing solar energy conversion and overall performance.…”
Section: Solar Integration In Combined Power Plants and Research Ques...mentioning
confidence: 99%
“…Benabdellah et al [16] analyzed, from a thermodynamics point of view, the energy, exergy, and economics of an integrated solar combined cycle (ISCC) power plant situated in Algeria. It was made of two gas turbines of 40 MW each, one steam turbine of 80 MW, which was fed by two HRSGs (heat recovery steam generators), one solar steam generator (SSG), and a solar field of a total area of 183.120 m 2 and comprising 224 parabolic trough collectors (PTC).…”
Section: Introductionmentioning
confidence: 99%
“…Another way to increase the efficiency, sustainability and reduce fuel consumption of these systems is to use thermal storage to store some of the solar energy when radiation increases, which reduces the environmental effects and operating costs of these cycle. 24 In the field of emergy based analysis, there are a few studies have been performed. For the first time, Aghbashloo and Rosen 25 reformulated exergoeconomic and exergoenvironmental approaches using the emergy concept.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to increase the efficiency, sustainability and reduce fuel consumption of these systems is to use thermal storage to store some of the solar energy when radiation increases, which reduces the environmental effects and operating costs of these cycle. 24…”
Section: Introductionmentioning
confidence: 99%